Analysis of radiation patterns and feed illumination of the reflector antenna using the physical and geometrical optics - Merabtine, N.; Boualleg, A.; Benslama, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Reflector antennas are characterized by very high gains (30 dB and higher) and narrow main beams. They are widely used in satellite and line-of-sight microwave communications as well as in radar. Reflector antennas operate on principles known long ago from the theory of geometrical optics. The first reflector system was made by Hertz back in 1888 (a cylindrical reflector fed by a dipole). The radiation fields from aperture antennas, such as slots, open-ended waveguides, horns, reflector and lens antennas, are determined from the knowledge of the fields over the aperture of the antenna. In this paper, we analyzed the effects of feeds relating to the parabolic reflectors such as waveguide and horn. We show the variations of the gain in the electric and magnetic planes (E and H) according to the angle of incidence. In our case, we use the origin to be at the focus.